Early-Onset Vascular Leukoencephalopathy Caused by Bi-Allelic NOTCH3 Variants - Stellingwerff, Menno D.; Nulton, Corinne; Helman, Guy; Roosendaal, Stefan D.; Benko, William S.; Pizzino, Amy; Bugiani, Marianna; Vanderver, Adeline; Simons, Cas; van der Knaap, Marjo S. (Neuropediatrics, 2022)
Objective Heterozygous NOTCH3 variants are known to cause cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), with patients typically presenting in adulthood. We describe three patients presenting at an early age with a vascular leukoencephalopathy. Genome sequencing revealed bi-allelic variants in the NOTCH3 gene.Methods Clinical records and available MRI and CT scans of three patients from two unrelated families were retrospectively reviewed.Results The patients presented at 9 to 14 months of age with developmental delay, seizures, or both. The disease course was characterized by cognitive impairment and variably recurrent strokes, migraine attacks, and seizures. MRI findings pointed at a small vessel disease, with extensive cerebral white matter abnormalities, atrophy, lacunes in the basal ganglia, microbleeds, and microcalcifications. The anterior temporal lobes were spared. Bi-allelic cysteine-sparing NOTCH3 variants in exons 1, 32, and 33 were found.Interpretation This study indicates that bi-allelic loss-of-function NOTCH3 variants may cause a vascular leukoencephalopathy, distinct from CADASIL.
Keywords: NOTCH3; leukoencephalopathy; small vessel disease